Global trends in molecular epidemiology of HIV-1 during 2000-2007 - Hemelaar, Joris (2011)
Objective To estimate the global and regional distribution of HIV-1 subtypes and recombinants between 2000 and 2007. Design Country-specific HIV-1 molecular epidemiology data were combined with estimates of the number of HIV-infected people in each country. Method Cross-sectional HIV-1 subtyping data were collected from 65913 samples in 109 countries between 2000 and 2007. The distribution of HIV-1 subtypes in individual countries was weighted according to the number of HIV-infected people in each country to generate estimates of regional and global HIV-1 subtype distribution for the periods 2000–2003 and 2004–2007. Results Analysis of the global distribution of HIV-1 subtypes and recombinants in the two time periods indicated a broadly stable distribution of HIV-1 subtypes worldwide with a notable increase in the proportion of circulating recombinant forms (CRFs), a decrease in unique recombinant forms (URFs), and an overall increase in recombinants. In 2004–2007, subtype C accounted for nearly half (48%) of all global infections, followed by subtypes A (12%) and B (11%), CRF02_AG (8%), CRF01_AE (5%), subtype G (5%) and D(2%). Subtypes F, H, J and K together cause fewer than 1% of infections worldwide. Other CRFs and URFs are each responsible for 4% of global infections, bringing the combined total of worldwide CRFs to 16% and all recombinants (CRFs plus URFs) to 20%. Conclusions The global and regional distributions of individual subtypes and recombinants are broadly stable, although CRFs may play an increasing role in the HIV pandemic. The global diversity of HIV-1 poses a formidable challenge to HIV vaccine development.